Threshold cointegration and interest rate pass - through during the pre - and post - banking consolidation in Nigeria: are there asymmetries? - Aliyu, Alhaji Jibrilla; Ismail, Normaz Wana (Inderscience Publishers, 2016)
This paper empirically examines the interest rate pass-through in Nigeria using the cointegration and threshold adjustment suggested by Enders and Siklos. The focus is on the pass-through of the central bank policy rates to the commercial banks' lending rates during the pre- and post-bank consolidation in the country. The estimated results indicate that, changes in the policy rate are transmitted completely to loans rate in the long run during the pre-cosolidation but incomplete during the post-consolidation period. The results also show evidence for asymmetric momentum threshold autoregression models during the both the pre-and post-consolidation periods. However, while the estimated nonlinear error correction models exhibit downward rigidity in lending rates during the pre-consolidation, a contrary finding was obtained during the post-consolidation period, which indicates upward rigidity of loans rates. Finally, the study discusses the potential implication of these findings on the banking sector and offers direction for future policy.